A quantitative analysis of the prevalence of clinical depression and anxiety in patients with prostate cancer undergoing active surveillance. Issue 5 (22nd May 2015) - Watts, Sam; Leydon, Geraldine; Eyles, Caroline; Moore, Caroline M; Richardson, Alison; Birch, Brian; Prescott, Philip; Powell, Catrin; Lewith, George
Abstract : Objective: To quantitatively determine the prevalence of anxiety and depression in men on active surveillance (AS). Design: Cross-sectional questionnaire survey. Setting: Secondary care prostate cancer (PCa) clinics across South, Central and Western England. Participants: 313 men from a total sample of 426 with a histological diagnosis of PCa currently managed with AS were identified from seven UK urology departments. The mean age of respondents was 70 (51–86) years with the majority (76%) being married or in civil partnerships. 94% of responders were of white British ethnicity. Primary outcome measures: The prevalence of clinically meaningful depression and anxiety as assessed by the Hospital Anxiety and Depression Scale (HADS; score ≥8/21). Secondary outcome measures: Patient demographic data (age, employment, relationship, ethnic and educational status). Each demographic variable was cross-tabulated against patients identified as depressed or anxious to allow for the identification of variables that were significantly associated with depression and anxiety. In order to determine predictors for depression and anxiety among the demographic variables, logistic regression analyses were conducted, with p<0.05 considered as indicating statistical significance. Results: The prevalence of clinical anxiety and depression as determined via the HADS (HADS ≥8) was 23% (n=73) and 12.5% (n=39), respectively. Published data from men in the general population of similar age has shown prevalence rates of 8% and 6%, respectively, indicating a twofold increase in depression and a threefold increase in anxiety among AS patients. Our findings also suggest that AS patients experience substantially greater levels of anxiety than patients with PCa treated radically. The only demographic predictor for anxiety or depression was divorce. Conclusions: Patients with PCa managed with AS experienced substantially higher rates of anxiety and depression than that expected in the general population. Strategies to address this are needed to improve the management of this population and their quality of life.